The Yin And Yang Of Csr Ethical Branding - Nasruddin, Ellisha; Bustami, Reevany (Asian Academy of Management (AAM), 2007)
Within the current discourse and the often overly-commercialized hyperbole of branding and positioning, there is a particular area that has not been given due attention. Yet, with the rapid changes and the multiple crises of present-day realities, a frequently neglected area, emerges as vitally imperative. The troubles can be seen in both large as well as small businesses within Malaysia. This article, thus, aims to bring back ethics, one of the management blind-spots, into the center stage of branding and organizational transformation. The objectives of this article are two-fold: (1) to build a discussion on the value and importance of ethical branding through CSR initiatives and (2) to present a CSR ethical branding (CSR-EB) framework which delineates the content (yin) and context (yang), comprising seven pillars: pillar of ethical core, pillar of inner stakeholders, pillar of products and services, pillar of outer stakeholders, pillar of cultural context, pillar of spatial context, and pillar of temporal context.